Kriptografi Teks Berbasis Algoritma Substitusi Vigenere Cipher 8 Bit - Nida Aulia Karima; Ade Nurul Aisyah; Hercio Venceslau Silla; Lekso Budi Handoko; Ramadhan Rakhmat Sani (Department of Informatics, Universitas Diponegoro, 2024)
Vigenere Cipher is one of the classic cryptographic algorithms in the world of cryptography. This research focuses on the use of the Vigenere Cipher method and its implementation in securing an ASCII message text. This research uses four testing methods namely, Avalanche Effect, Character Error Rate (CER), Bit Error Rate (BER), and Entropy. The test results found that the Avalanche Effect value produced on average was at 50% and above, meaning that a good Avalanche Effect value was obtained. In addition, the resulting CER and BER are 0, meaning that no errors occurred during the encryption process. The resulting Entropy value also increases along with the length of the plaintext used and is also influenced by the use of ASCII 256 in the form of letters, numbers, and symbols.